THE ROLE OF PUBLIC SUPERVISORS IN IMPLEMENTING THE ASSIMILATION AND INTEGRATION OF PROVIDERS IN COVID-19 - Marlan Parakas (Polteknik Ilmu Pemasyarakatan, 2020)
Expenditures of prisoners with assimilation and integration during the Covid-19 Pandemic had an impact on new problems and without any assessment carried out by Community Advisors as one of the conditions. The problem raised was how the role of Community Guides in the implementation of assimilation and integration of prisoners during the Covid-19 Pandemic. The theory used is policy theory and descriptive qualitative research methods by describing the impact of assimilation and integration on prisoners. The results of the research show that presenting assimilation and integration for inmates during the Covid-19 pandemic experienced problems in society with the presence of several prisoners who did this and this also occurred due to the lack of implementation by social advisers.